2013
DOI: 10.1016/j.healun.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Persistent strong anti-HLA antibody at high titer is complement binding and associated with increased risk of antibody-mediated rejection in heart transplant recipients

Abstract: BACKGROUND Sensitized heart transplant candidates are evaluated for donor-specific anti-HLA IgG antibody (DSA) by Luminex single-antigen bead (SAB) testing (SAB-IgG) to determine donor suitability and help predict a positive complement-dependent cytotoxicity crossmatch (CDC-XM) by virtual crossmatching (VXM). However, SAB testing used for VXM does not correlate perfectly with CDC-XM results and individual transplant programs have center-specific permissible thresholds to predict crossmatch positivity. A novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
137
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 12 publications
12
137
1
Order By: Relevance
“…47 However, another study found C1q+DSA more likely to be of DQ specificity and also, associated with a 30% decrement in 5-year survival. 84 To bind complement, antibodies must be IgG1/3 isotope and be of sufficiently high titer; closer examination of these studies and others indicates that antibody amount (estimated albeit imperfectly by MFI) is the major predictor of C1q positivity and outcomes, 48,[84][85][86][87]117 and the role of this new assay in addition routine SAB testing remains to be fully determined.…”
Section: Dndsa and Features Of Amrmentioning
confidence: 99%
“…47 However, another study found C1q+DSA more likely to be of DQ specificity and also, associated with a 30% decrement in 5-year survival. 84 To bind complement, antibodies must be IgG1/3 isotope and be of sufficiently high titer; closer examination of these studies and others indicates that antibody amount (estimated albeit imperfectly by MFI) is the major predictor of C1q positivity and outcomes, 48,[84][85][86][87]117 and the role of this new assay in addition routine SAB testing remains to be fully determined.…”
Section: Dndsa and Features Of Amrmentioning
confidence: 99%
“…This is based on our previous findings that IgG3 subclass DSA was an independent risk factor for allograft loss (26) and recent studies in kidney and heart transplantation that showed C1q testing, detected using a sensitive bead assay, was able to identify DSAs associated with the lowest survival and highest rejection rate (30,31). However, IgG3 subclass and C1q testing do not necessarily document the in vivo pathologic potential of IgG3 subclass DSA and complement fixing DSA, and instead may simply represent either more evolved alloimmune responses or simply more specific tests.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assays measure binding of C1q (45) or deposition of C3d (46) or C4d (47,48) to single-antigen beads, enabling identification of potentially complement-activating antibodies as well as their HLA specificity. The prognostic value of these assays remains controversial (5, 7, 20, 49-52), in part because in vitro complement activity appears to be tightly tied to antibody titer (20,44,53,54).…”
Section: Neutrophil Marginationmentioning
confidence: 99%